2013
DOI: 10.1002/prep.201300070
|View full text |Cite
|
Sign up to set email alerts
|

Application of Azido Esters as Energetic Plasticizers for LOVA Propellant Formulations

Abstract: The study of a cyclotrimethylene trinitramine‐based low vulnerable ammunition (LOVA) propellant having cellulose acetate (CA) and nitrocellulose (NC) combinations as binders is described herein. Two propellant compositions (1 and 2) were prepared by replacing the non energetic plasticizer triacetin (TA) with the novel tetraazido ester plasticizers tetraazido malonate and tetraazido glutarate, respectively, and their ballistic, mechanical, and thermal properties were studied. Both compositions 1 and 2 showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 16 publications
1
26
0
Order By: Relevance
“…Then, it could be concluded that ABAMPA is much insensitive than TAP‐Ac, which was also confirmed by the friction sensitivity (FS) results of ABAMPA (324 N) and TAP‐Ac (54 N) . Besides, the impact and friction sensitivities of ABAMPA were comparable if not less than some previously reported azido ester plasticizers, such as BAEM, BAEG and 1,5‐diazido‐3‐nitrazapentane (DIANP) ,,. Therefore, the insensitivities toward impact and friction of ABAMPA is proved experimentally.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…Then, it could be concluded that ABAMPA is much insensitive than TAP‐Ac, which was also confirmed by the friction sensitivity (FS) results of ABAMPA (324 N) and TAP‐Ac (54 N) . Besides, the impact and friction sensitivities of ABAMPA were comparable if not less than some previously reported azido ester plasticizers, such as BAEM, BAEG and 1,5‐diazido‐3‐nitrazapentane (DIANP) ,,. Therefore, the insensitivities toward impact and friction of ABAMPA is proved experimentally.…”
Section: Resultssupporting
confidence: 68%
“…Energetic plasticizers (EPs) are often preferred to inert plasticizers because EPs perform a dual task: retaining reasonable sensitivity, suppressing chemical reactivity, and ensuring a high thermal stability as one approaches oxygen balanced materials, creating the densest material possible. In order to increase the energy level of propellants, energetic groups such as nitro, difluoramino, nitramino, and azido groups are introduced into some molecular structures to design novel high energetic plasticizers …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both inert and energetic plasticizers have involved propellant and explosive formulations to improve process parameters, mechanical properties and insensitivity properties of them . 1,2,4‐Butanetriol trinitrate, trimethylolethane trinitrate, nitroglycerin, n ‐butyl‐2‐nitratoethyl‐nitramine, triethyleneglycol dinitrate, and bis(2,2‐dinitropropyl)acetal or formal are energetic plasticizers used in especially smokeless or reduce smoke propellant formulations to compensate energy loss due to reduction or removal of metallic fuel which is responsible for primary smoke generation.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature [8,9], common LOVA propellants contain about ~10% nitrocellulose, ~15% plasticizers and ~75% RDX, so a similar formulation was used as starting point. To observe the influence of the various materials, other solutions were prepared by reducing the amount of RDX relative to the other compounds.…”
Section: Preparation Of the Solutionsmentioning
confidence: 99%